Interactions between financial efficiency and sports performance: Data for a sustainable entrepreneurial approach of European professional football clubs - Miragaia, D. A. M. (2020)
Purpose – In the current economic climate, the huge rise in the levels of debt incurred by professional football clubs challenges the need to improve their efficiency levels. Hence, analysis of their productivity is essential and represents an integral dimension to any realistic and efficient strategy. Any such strategy includes the identification and analysis of the inputs and outputs that underpin club sustainability. The purpose of this paper is to evaluate the relationship between the team performance of professional European football clubs and the stability of their financial efficiency. Design/methodology/approach – The sample spans 15 professional football clubs that won the league titles in the leading football leagues (the English, German, Spanish, Italian and French leagues) in the period between 2009 and 2014. The analysis made recourse to the data envelopment analysis method. Findings – The results demonstrate that of the 15 clubs analysed, only 10 proved efficient. Football is now an industry that moves major quantities of financial capital and holds the attentions of large groups of fans worldwide. However, despite this attractiveness, the financial crisis and recession, ongoing since 2008, increasingly requires the better management of such resources. To this end, clubs should improve their control over the financial resources available given the positive relationship prevailing between the sporting performance of clubs and their levels of financial efficiency. Originality/value – Analysis of the efficiency levels of the inputs and outputs encapsulating performance related financial variables may aid in improving the standards of planning and sustainable management at professional sport clubs.